Role of procalcitonin as a predictor of clinical outcomes in hospitalized patients with COVID-19 - Ian Jackson; Hadi Jaradeh; Sarah Aurit; Ali Aldamen; Shraddha Narechania; Christopher Destache; Manasa Velagapudi (International Journal of Infectious Diseases, 2022)
Objectives: In this study, we aimed to determine the correlation between procalcitonin (PCT) levels and clinical outcomes including in-hospital mortality, intensive care unit (ICU) length of stay, and hospital length of stay in patients hospitalized with COVID-19. Methods: Clinical, laboratory, and demographic data of 223 patients who met inclusion criteria were analyzed. PCT measurements of 0.25 ng/mL and 0.50 ng/mL were used to stratify patients into 2 mutually exclusive groups. Results: Patients with PCT above 0.25 ng/mL on admission had significantly elevated Acute Physiology and Chronic Health Evaluation II scores (9 vs 8; P = 0.042) and C-reactive proteins levels (111 μg/mL vs 79 μg/mL; P = 0.007). A multivariable binary logistic regression model demonstrated no relationship between PCT and mortality (OR = 1.00; 95% Cl: 0.97 to 1.02; P = 0.713). Kaplan-Meier analysis revealed no statistical evidence of a difference between PCT groups and hospital length of stay (P = 0.144 for 0.25 ng/mL, P = 0.368 for 0.50 ng/mL) or intensive care unit length of stay (P = 0.986 for 0.25 ng/mL, P = 0.771 for 0.50 ng/mL). Conclusions: Elevated PCT levels were associated with severity of illness but did not correlate with in-hospital mortality, hospital length of stay, or ICU length of stay.